Poverty Orderings when Welfare Comparisons are Uncertain. - Dercon, S (Department of Economics (University of Oxford), 2001)
In applied welfare economics, equivalence scales for household composition and size corrections, and appropriate price deflators are minimum requirements to perform interhousehold comparisons of welfare, measured via household income or consumption information. In practice, the information available is insufficient and only approximate price or household composition corrections are available. Poverty comparisons between groups or over time are then problematic. In this paper, Atkinson's standard results on first order stochastic (welfare) dominance are extended to allow for pairwise comparisons of poverty of groups with different needs or facing different prices, when there is uncertainty on the true cost-of-living deflators and equivalence scales. The approach is illustrated using household surveys from Ethiopia and Burkina Faso.